Strengthening Students’ Basic English Skills Through Collaborative Fun Learning at Madrasah Diniyah Takmiliyah Awaliyah - Fitri Rachmiati Sunarya; Moch Trisq Arsyil Mufid; Rifqi Fahrezi; Muh Syahril Sidiq (Penerbit Goodwood, 2026)
Purpose: This community service program aims to improve students' basic English skills at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Amaliyah, Indramayu, through fun learning methods. It was initiated because of students' low interest and confidence in learning English, caused by conventional approaches. Methodology: The program was conducted at MDTA Amaliyah, Gaunter District, Indramayu Regency, involving 45 students aged 7–9 years. Activities included observation, coordination with teachers, material preparation, and interactive learning using singing, games, illustrated guidebooks, and simple conversation exercises. Evaluation was performed through pre-test and post-test quizzes and observations of student participation. Results: The program led to improvements in students' English skills, particularly in pronunciation, vocabulary recognition, and participation confidence. Conclusions: The fun learning-based program was effective in enhancing MDTA students' basic English skills, including vocabulary, pronunciation, and learning participation, making it suitable for early students in madrasah diniyah. Limitations: The short duration and limited sample size mean that the findings represent only short-term effects and may not be widely generalizable. Contributions: This study reinforces the effectiveness of fun learning methods in early childhood English education and provides a practical learning model for madrasas with limited resources.